Six newly recorded plant species in Zhejiang Province - CHEN Lichun; CHEN Zhenghai; MA Dandan; LIN Hailun; LI Xiupeng; LI Genyou (浙江大学学报. 农业与生命科学版, 2016)
During the investigation of coastal plants in Ningbo, several species were discovered, which cannot be classified into any species previously reported in the flora of Zhejiang. Based on further comparison and information review, these species belonging to six genera in six families were identified as new records of Zhejiang Province, including Ophioglossum reticulatum Linn. (Ophioglossaceae), Gomphrena celosioides Mart. (Amaranthaceae), Nuphar sinensis Hand.-Mazz. (Nymphaeaceae), Gratiola japonica Miq. (Scrophulariaceae), Gynostemma laxum(Wallich) Cogniaux (Cucurbitaceae) and Lycoris albiflora Koidz. (Amaryllidaceae). Gratiola Linn. is a new record genus of Zhejiang Province.The discovery of these newly recorded plants enriched the content of flora of Zhejiang Province and provided fundamental materials for investigating their geographical distributions in China.